Potential policy impacts: Establishment of Indonesian mining state-owned holding company - Chandra Wijaya; Rina Andriani (Jurnal Ilmiah Ilmu Administrasi Publik, 2019)
Government of Republic of Indonesia has been working to establish and operate the State-Owned Holding Company for Mining sector. There has been a long debate in whether in public, government institution, even in the industry on how this policy would give impact to all stakeholders within the business. While this mining state-owned holding company keep going on its mission to achieve the policy’s objectives, in order to monitor the track we are at, this paper is trying to observe on the potential policy impacts and how can we manage to solve any damage, if there is any, so that the negative implications from the policy can be understood better and well handled by the government as well as the holding.